The effect of crest shape on discharge coefficient at linear weirs - Dogan, Yusuf; Kaya, Nihat (Croatian Association of Civil Engineers, 2023)
A detailed experimental laboratory analysis of the effect of crest shape on the discharge coefficient of sharp-crested weirs is presented in the paper. The experiments were conducted for four different crest shapes. The experiments and analyses show that discharge capacity, and discharge coefficient in particular, are significantly affected by weir crest height. It is stated in conclusion that rounded crest shape has the highest discharge capacity. In practice, sharp crested weirs are generally preferred to other crest shapes due to construction facility, although the discharge coefficient values of sharp crested weirs are lower compared to rounded crest shape. © 2023, Croatian Association of Civil Engineers. All rights reserved.
Utjecaj oblika krune na koeficijent prelijevanja linearnih preljeva
Keywords: crest shape; discharge capacity; discharge coefficient; open channel flow; weir